Dermocosmetic properties of bioproducts from Sargassum macroalgae: chemical aspects, challenges, and opportunities - Cunha dos Santos, Thalisia; Pompermayer Machado, Levi; Pimentel Santos, Ana Luíza Vidal; Campos Martins, Roberto Carlos; Cavalcanti, Diana Negrão; Wolff Bueno, Guilherme; Madeira Sanches, Ana Letícia; Concha Obando, Johana Marcela (Frontiers in Marine Science, 2024)
The cosmetics industry is experiencing continuous growth and the search for dermoactive metabolites continues to increase, positioning natural marine products as an essential element in this market. The genus Sargassum, a cosmopolitan brown alga, stands out for its diversified arsenal of metabolites with biological properties of great interest for the cosmetic sector. This study presents an updated review of the dermocosmetic properties of 17 Sargassum species published between 2020 and 2024, emphasizing increasing interest in its antioxidant and photoprotective properties. Furthermore, the review highlights the crucial role of green extraction methodologies, such as ultrassom-assisted extraction (EAU), enzyme-assisted extraction (EAE) and microwave-assisted extraction (MAE). It is also provided a conceptual outline of the spectrometric analytical techniques used for characterization of extracts and identification of active composts, such as polysaccharides (alginate and fucoidane), phenolic composts (phlorotannins and phenylpropanóids) and terpenoids (diterpenoids, saponins and norisoprenóids). In addition to addressing bioprospecting and the potential of the biorefinery in the cosmetics sector, this review analyzes challenges related to quality control of raw materials, seasonal fluctuations of seaweed and regulations governing the collection and use of seaweed. To provide a detailed update on the dermocosmetic potential of these algae, the review aims to support future research and encourage bioprospection of this biomass as a sustainable and promising source for the development of new bioproducts.